Microstructure and heat transfer characteristics of active brazed Ceramic–Metal joints. Issue 11 (1st June 2021) - Sivaprahasam, D.; Sujitha, T.; Gowtham, U.; Jayachandran, B.; Gopalan, R.
Abstract: This work reports on the bonding of Al2 O3 –Cu, AlN–Cu, and AlN–Ni by active brazing for the thermoelectric module support plate. Ag63 Cu35.25 Ti1.75 braze alloy in the form of paste and sheet was used for this purpose. Investigation of the microstructure using scanning electron microscope (SEM) attached with energy dispersive spectroscopy (EDS) showed that Al2 O3 –Cu brazed joint alone had an interface with a continuous reaction layer. On the other hand, AlN when brazed to Cu and Ni showed a relatively weak bonding due to the poorly developed reaction layer at the interface. The growth of reaction layer while brazing of AlN–Cu and AlN–Ni was impeded by the dissolution of the respective metals into the molten braze alloy. In AlN–Ni, the decrease in Ti activity due to such dissolution is so low that the interface reaction layer was absent. The temperature difference ( ΔT ) measured across the ceramic–metal joints showed little resistance to heat transfer in Al2 O3 –Cu. On the other hand, other joints have shown a significant ΔT, mainly due to the poorly developed and less thermally conductive (TiAl)1+x N interface reaction layer. Thus, this study demonstrates that a stable ceramic–metal joint with high thermal conductivity could be made with Al2 O3 using Cu by active brazing.